Group Mentorship Model to Enhance the Efficiency and Productivity of PhD Research Training in Sub-Saharan Africa. Issue 1 (30th April 2018) - Manabe, Yukari C.; Nambooze, Harriet; Okello, Elialilia S.; Kamya, Moses R.; Katabira, Elly T.; Ssinabulya, Isaac; Kaddumukasa, Mark; Nabunnya, Yvonne; Bollinger, Robert C.; Sewankambo, Nelson K.
Introduction: High quality PhD training in sub-Saharan Africa is important to strengthen research evidence to advance development and health. Training a critical mass of independent investigators capable of original scientific research requires strong mentorship, research environments, and international networks. We sought to iteratively improve a PhD training model in Uganda through systems capacity building. Methods: PhD students were selected through a rigorous competitive application and selection process, which included a written proposal and a face-to-face panel interview. The program provided administrative support, paid tuition fees, tools (space, equipment, research money), skills (short research courses on study design, biostatistics, manuscript and grant writing), and infrastructure (finance, grants management support, and lab infrastructure). Guidance to identify local and international mentorship was also provided in addition to two to three group meetings per year where data was presented and progress assessed by the program leaders in addition to available local mentors. Results: Seventeen PhD students were selected, and fifteen will complete training through the MEPI-MESAU program. To date, 60% have completed, including 2 students who started 2 years into the program. So far, 169 publications have been published in the peer-reviewed literature. Our PhD students have supervised and mentored 65 Master's students, which illustrates the cascade effect of PhD training on the academic medical school environment. Conclusions: The systems capacity building approach to PhD training is an efficient and productive training model that allowed strong outputs at lower cost and with relatively few additional mentors to rapidly achieve a critical mass of independent scientists able to conduct original research and mentor others.